The effects of different diets on survival of marine oligochaetes worm (Oligochaeta: Tubificidae) - Zakirah, Mohamad T.; Shabdin, Mohd Long; Khairul-Adha, A. Rahim; Fatimah-A’tirah, Mohamad; Ahmad-Nasir, Ahmad S. (Bioflux, 2016)
This experiment is designed to observe the suitability of different diets on survival rate of marine oligochates worm in laboratory scale using flowing water system. The oligochaetes worms were cultured in five different diet treatments (commercial pellet, seaweed, goat dung, soybean meal and combination diet) each having triplicates. The oligochaetes were cultured for 90 days. The highest survival rate of oligochaetes culture were found significant (p < 0.001) in the combined diet containing goat dung (20%), seaweed (Gracilaria sp.: 20%) and soybean meal (20%). Results of the present study suggest that the combination diet is the best compared to single diet in order to obtain the maximum survival rate of marine oligochaetes worm. The present finding is important in providing the baseline data for marine oligochaetes culture. Further study might be extended in detail to investigate the reproductive cycle since marine oligochaetes is highly potential in mass culture production.